An empirical study on the potential of land resources utilization in urban agglomeration development zones based on combination analysis - Miao, Jianjun; Lu, Qian (Earth Sciences Research Journal, 2021)
To alleviate the contradiction between human and land caused by the limitation of land resources and the irreversibility of land use in the development zone of urban agglomeration, 24 indexes were selected from four aspects: land use status, resource security, economic feasibility, and social acceptability to establish the level evaluation index system for the sustainable use of land resources in Baoding high-tech zone; also, the combination weighting method was used to determine the development level. The index weight of land resource utilization potential in the development zone was established. The subjective and objective linear combination was also established to obtain the proportion of subjective and objective. The multi-factor comprehensive evaluation model was used to evaluate the sustainable utilization degree of land in the high-tech zone. The comprehensive analysis of land-intensive use potential was made from five aspects: expansion potential, structure potential, intensity potential, management potential, and the number of years of land available; the analysis of the limiting factors and the combination of these factors of the land in the development zone was made to obtain the natural index after the renovation, and the natural quality potential of the cultivated land renovation was obtained according to the difference of the natural index before and after the renovation. The empirical results show that the high-tech zone’s land-use rationality index is relatively high during 2014-2018. During the evaluation period, the index continued to rise; the high-tech zone's resource security score was low, and there was no change during the evaluation period, which is basically at a low level. During the five years, the high-tech zone’s land-use sustainability has experienced the fluctuation process of first rising and then declining, which is in the stage of medium sustainable development. In the future, the potential for improvement is enormous. The prospect of the high-tech zone’s exploitable land structure is small, and the land structure is relatively reasonable, which is in line with the development orientation of the high-tech site. But the industrial land intensity in the zone also has a specific potential for excavation. The high-value areas of the natural quality potential of the land improvement in the high-tech site are mainly distributed in the west, northeast, and a few in the north and south.